Legal Status, Rights, And Inheritance Of Illegitimate Children Under Hindu, Muslim, And Christian Personal Laws In India: A Comparative Analysis. - Kumar Dixit, Akhilesh; Gupta, Neeru (Journal of Neonatal Surgery, 2025)
India’s pluralistic legal system, comprising personal laws for Hindu, Muslim, and Christian communities alongside secular statutes, creates a complex framework for the rights of illegitimate children—those born outside wedlock or from void/voidable marriages. These laws govern their legal status, entitlement to maintenance, guardianship, and inheritance, with significant variations across religious lines. This research paper provides an exhaustive comparative analysis of these rights under the Hindu Marriage Act, 1955 (HMA)1, Muslim personal law (Sharia-based), Christian laws (via the Indian Divorce Act, 1869)2, and secular provisions like the Code of Criminal Procedure, 1973 (CrPC)3, and Guardians and Wards Act, 1890 (GWA)4. It examines statutory frameworks, judicial interpretations, parental roles, socio-legal challenges, and the impact of secular overrides. The paper proposes reforms, including a uniform civil code, to ensure equitable treatment, aligning with Article 14’s equality mandate and international child rights standards..